USE OF CROWDFUNDING IN THE REGIONAL DEVELOPMENT PROCESS (Third Sector Social Economic Review, 2023)
Crowdfunding refers to the collection of small amounts of funds from many individuals for the development of an existing or socially beneficial event or early-stage initiative. is coming. With the 2008 global crisis, the difficulties in accessing finance increased the popularity of the crowdfunding system and the use of the crowdfunding system has become increasingly widespread. It is important to benefit from the crowdfunding financing method, which is becoming increasingly popular in developed and developing countries, in the regional development process. In this study, in which the benefits of using crowdfunding in regional development projects are revealed through a literature study, it has been seen that the crowdfunding system is not utilized in the regional development process in Turkey and there is no academic study on the subject. This study aims to reveal the contributions of the use of crowdfunding systems as an alternative financing source in regional development policies to the regional development process. Considering that there are differences in the quality of life between the regions of Turkey, it is possible to say that the use of the crowdfunding financing method as an additional tool to the existing financing tools in reducing the differences between regions in Turkey can increase the success of regional/local development projects. As a result of the study, it was concluded that the use of the crowdfunding system in reducing regional imbalances in Turkey will have significant effects on regional inequalities.
Keywords: Crowdfunding; Regional Development; Rural Development; Alternative Financing Techniques; Development Financing